Implementing and Analysis of SSL Protocol - Indrani Mukherjee (Journal of Electronic Design Engineering, 2018)
Safety risks are a prime issue, because the network workstations and programs are exposed to a diffusion of threats. The threats can be masquerading and replaying. To avoid these threats answers like handshake mechanism, authentication, authorization and cryptography can be used. The main goal of the task is to design and increase safety framework encapsulating the above solutions. This assignment addresses the QoS traits specifically security, maintainability and adaptability troubles within the designed system.